Homosexualities, Muslim cultures and modernity - Rahman, Momin (Palgrave Macmillan, 2020)
Contents: 1. In Search of My Mother's Garden: Reflections on Migration, Gender, Sexuality and Muslim Identity -- 2. Islam versus Homosexuality as Modernity -- 3. Problematic Modernization: the Extent and Formation of Muslim Antipathy to Homosexuality -- 4. Traditions and Transformations of Muslim Homoeroticism -- 5. Queer Muslims in the Context of Contemporary Globalized LGBTIQ Identity -- 6. The Politics of Identity and the Ends of Liberation -- 7. Beginnings.